The height premium in earnings: the role of physical capacity and cognitive and non-cognitive skills - Petter Lundborg; Paul Nystedt; Dan-Olof Rooth (Institute for the Study of Labor (IZA), 2009)
The association between stature and favorable labor market outcomes has been extensively documented. Recent studies have attributed this height premium to cognitive and social skills. We offer an alternative explanation, where the premium mainly arises from the positive association between height and physical capacity. Accounting for the latter reduces the height premium by about 80 percent. By also accounting for cognitive and non-cognitive skills, we are able to explain the entire height premium. Our estimates are based on data from the military enlistment register that has been linked to earnings for the entire population of Swedish males aged 28-38 in 2003.
urn:nbn:de:101:1-2009080761
Keywords: J10; J70; 330; Earnings; height premium; cognitive and non-cognitive skills; physical capacity; Lohndifferenzierung; Anthropologie; Kognition; Gesundheit; Schweden